Pengaruh Transformasi Media Pembelajaran Siswa pada Masa Pandemi Covid-19 - Juniarti, Mira Deva Tri; Sari, Siti Maya; Nurhayati, Nurhayati; Saputra, Jeki; Verliansyah, Rycko (JOEAI (Journal of Education and Instruction), 2021)
The orientation of this research is to explain and analyze changes in learning media in learning practices before and after the covid19 pandemic. Media is one of the supports in the learning process. This study uses a qualitative field survey method. Observation guidelines were enforced by implementing strict health protocols at the study site. And the interview method used in this research is an unstructured interview technique (detailed interview). The results of the study, the success or failure of the learning process is very dependent on the media used. Education is one aspect of being used as a forum to shape the character of the nation's children. Therefore, in the educational process an educator must be able to master various learning media, at SMP Negeri 07 Seluma in the learning process before the covid-19 pandemic, using focus media, whiteboards and a set of learning equipment commonly found in classrooms, using the learning media has greater effectiveness. In conclusion, the use of learning media before the covid-19 pandemic provided greater learning effectiveness because teachers were able to freely provide assessments that were assessed from cognitive, affective and psychomotor aspects to students than the learning media used during the current covid-19 pandemic, which used media social media as online learning media. Keywords: Learning Media, Covid-19 Pandemic